Study of the influence of acid etching treatments on the superficial characteristics of Ti - Chrcanovic,Bruno Ramos (2014)
Modifications in texture and surface chemistry are commonly used to increase the biologic response to implants. We evaluated the influence of five different acid etching treatments on the chemical and topographical superficial characteristics of cpTi grade IV discs (test groups). One group of samples were only polished (control group). The samples were analyzed by electron microscopy (SEM, EDS), atomic force microscopy, and grazing incidence XRD. The acid etching treatments which produced higher values for the amplitude roughness parameters showed a combination of strong acids (HF and HCl/H2SO4) at high concentrations, with a relatively high temperature (≥ 60 °C) for a considerable time (≥ 60 min). Titanium and oxygen were the only elements detected by EDS on the surface in all groups, whereas titanium hydride was detected when the samples were analyzed by GIXRD. Only the group subjected to thermal treatment showed presence of rutile phase on the surface.